Impact of Immunosuppression on the Severity of SARS-CoV-2 Infection in Renal Transplant Recipients - Sandes Freitas, Tainá Veras de (2022)
Kidney transplant patients have a high case fatality rate following severe acute respiratory syndrome 2 (SARS-CoV-2) infection. In addition, the vaccine immune response is lower and less durable, whichmakes them more susceptible to severe forms, even when vaccinated. Evidence suggests that in addition to advanced age and the high prevalence of comorbidities often associated with worse prognosis, such as diabetes, obesity, and cardiovascular disease, prolonged immunosuppression exerts an independent effect on outcomes. In fact, the cellular and humoral adaptive immune response, which is inhibited by immunosuppression, is a key step in resolving SARS-CoV-2 infection. On the other hand, lymphocyte inhibition could modulate the aberrant production of proinflammatory cytokines that result in severe lung impairment, mitigating the severity of the condition. In addition, some immunosuppressive drugs have antiviralproperties, potentially applicable to coronavirus. This narrative review aimedto discuss the available evidence on the impact of immunosuppressive drugs on COVID-19 outcomes in kidney transplant recipients.